The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/elps.200700110
|View full text |Cite
|
Sign up to set email alerts
|

A rapid CZE method for the analysis of benzodiazepines in spiked beverages

Abstract: A rapid CZE method was developed for the simultaneous determination of nine benzodiazepines in spiked beverages (nitrazepam oxazepam, alprazolam, flunitrazepam, temazepam, diazepam, 7-aminoflunitrazepam, 7-aminonitrazepam and 7-aminoclonazepam). The method employed a double-coated capillary coated with poly(diallyldimethylammonium chloride) and then dextran sulphate. The BGE conditions were 100 mM ammonium phosphate buffer, pH 2.5, which gave baseline resolution between consecutive peaks and a run time of less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The drawbacks to these methods are that the times for the analysis are longer than 6 minutes per sample and a liquidliquid extraction prior to analysis is also needed. [14][15][16] Tu et al 8 reported an electrochemical impedimetric immunosensor for determining Ketamine in buffered samples. This method offers very low detection limits.…”
Section: Ketamine (K) [2-(-o-chlorophenyl)-2-(methylamino)-cyclohexanmentioning
confidence: 99%
“…The drawbacks to these methods are that the times for the analysis are longer than 6 minutes per sample and a liquidliquid extraction prior to analysis is also needed. [14][15][16] Tu et al 8 reported an electrochemical impedimetric immunosensor for determining Ketamine in buffered samples. This method offers very low detection limits.…”
Section: Ketamine (K) [2-(-o-chlorophenyl)-2-(methylamino)-cyclohexanmentioning
confidence: 99%
“…Gas chromatography (GC) has been widely used as well, in combination with mass spectrometry (MS) or with other detectors such as nitrogen-phosphorous (NPD) and micro-electron capture (ECD) [1 and references therein-2] Hyphenated GC techniques are very sensitive and specific, yet some BDZ are thermolabile and require derivatization prior to analysis [3,4]. Other approaches include micellar electrokinetic chromatography using a cyanine dye for indirect laser-induced fluorescence detection and capillary zone electrophoresis (CZE) [5]. Nonetheless, liquid chromatography (LC) is a commonly used technique, particularly when coupled with MS or ultraviolet (UV) detection [6].…”
Section: Introductionmentioning
confidence: 99%
“…While HPLC remains the most common technique for the analysis of benzodiazepines, 7,9,14,15 mainly in reversed phase (RP) mode, several capillary zone electrophoresis (CZE) methods have recently been developed. 2,16,17 CZE represents an interesting alternative to HPLC for determination of pharmaceuticals, in general, 18,19 mainly because of its higher efficiency in comparison with HPLC. 20 The aim of this work was to develop and optimize separation conditions for a set of seven 1,4-BZDs in RP-HPLC and CZE with UV detection and compare these methods in terms of efficiency, analysis time, resolution, elution order and basic validation parameters.…”
Section: Introductionmentioning
confidence: 99%